2022
DOI: 10.31083/j.jin2103078
|View full text |Cite
|
Sign up to set email alerts
|

Can cell and gene therapies improve cognitive symptoms in Parkinson’s disease?

Abstract: Advanced therapeutic medicinal products (ATMPs), including cell and gene therapies, are in development for Parkinson's disease (PD). In many cases, the goal is to replace the lost dopamine (DA), which is anticipated to improve motor dysfunctions associated with DA loss. However, it is less clear the extent to which these therapeutic interventions may impact on the wide range of cognitive symptoms that manifest as the disease progresses. Although the accepted perception is that cognitive symptoms are predominat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 85 publications
0
2
0
Order By: Relevance
“…The mesocortical dopaminergic circuit, which comprises the head of the caudate nucleus, rostral putamen, intermediate zone of subthalamic nucleus and the dorsolateral prefrontal cortex, is involved in higher cognitive, or executive, functions, whereas the mesolimbic dopaminergic circuit, which comprises the nucleus accumbens, ventromedial striatum, rostral ventral, ventromedial subthalamic nucleus and anterior cingulate cortex, is involved in reward processing and apathy/depression ( Hirano, 2021 ; Lelos, 2022 ; Meder et al, 2019 ). Disruption to the mesolimbic and mesocortical pathways in people with PD is consistent with PET imaging data that suggest reduced dopamine transmission in ventral striatal/nucleus accumbens regions and cingulate/prefrontal cortical areas.…”
Section: Unknown #3: Impact Of Dopaminergic Cell Therapies On Non-mot...mentioning
confidence: 99%
See 1 more Smart Citation
“…The mesocortical dopaminergic circuit, which comprises the head of the caudate nucleus, rostral putamen, intermediate zone of subthalamic nucleus and the dorsolateral prefrontal cortex, is involved in higher cognitive, or executive, functions, whereas the mesolimbic dopaminergic circuit, which comprises the nucleus accumbens, ventromedial striatum, rostral ventral, ventromedial subthalamic nucleus and anterior cingulate cortex, is involved in reward processing and apathy/depression ( Hirano, 2021 ; Lelos, 2022 ; Meder et al, 2019 ). Disruption to the mesolimbic and mesocortical pathways in people with PD is consistent with PET imaging data that suggest reduced dopamine transmission in ventral striatal/nucleus accumbens regions and cingulate/prefrontal cortical areas.…”
Section: Unknown #3: Impact Of Dopaminergic Cell Therapies On Non-mot...mentioning
confidence: 99%
“…Given that dopamine is associated with some aspects of cognitive and neuropsychiatric dysfunction in PD, it is reasonable to consider whether cell therapies may be capable of alleviating these symptoms ( Lelos et al, 2012 ; Lelos, 2022 ). Consistent with this hypothesis, work in rodent models of PD has shown that human and rodent foetal dopamine grafts can improve cognitive processing, visuospatial dysfunction and reward/motivational impairments ( Heuer et al, 2013a , b ; Lelos et al, 2016 ).…”
Section: Unknown #3: Impact Of Dopaminergic Cell Therapies On Non-mot...mentioning
confidence: 99%